Renal primitive neuroectodermal tumor: A rare case with a good prognosis - Chen, Hanmin; Li, Yanmin; Zeng, Qingming; Wu, Gengqing (Frontiers in Surgery, 2023)
Background: Renal primitive neuroectodermal tumor ( rPNET ) has the characteristics of difficult preoperative diagnosis, high degree of malignancy, easy early metastasis or postoperative recurrence, poor prognosis and so on. However, rPNET that without metastasis before surgery can have a good survival prognosis only after radical surgical resection. Methods: We reported a 14-year-old male patient with renal tumor, who underwent open radical left nephrectomy without radiotherapy or chemotherapy before and after surgery, and was confirmed by postoperative pathological results. The prognosis was followed up by regular review of chest and whole abdomen CT, hematuria analysis, renal function and electrolyte according to the guidelines for renal cancer. Results: Postoperative pathological results confirmed rPNET, no adjuvant radiotherapy and chemotherapy was performed after surgery, and no tumor recurrence and metastasis was observed during the follow-up of nearly 5 years. Conclusions: Despite the high level of rPNET malignancy, Patients without metastasis before surgery can still obtain a good survival prognosis through timely radical surgery.